PERANCANGAN BRAND COMMUNICATION UNTUK BISNIS ETHEREAL BESERTA MEDIA PROMOSINYA - Maria Laura Laurentine Judianto (Jurnal Vicidi, 2021)
Ethereal is a brand that sells handmade soap with an environmentally friendly concept, which puts forward natural ingredients that are safe for the skin and the environment. The design of the brand campaign and its promotional media is made as a means to communicate the value and products offered and to increase Ethereal brand awareness to potential consumers. The method used is primary data collection through interviews with three experts and three extreme users and distribution of questionnaires to 100 people who are using handmade soap. Research is also supported by literature studies, books, journals and previous research as secondary data. The results of the design are in the form of a campaign strategy and the selection of promotional media used, in accordance with the input and suggestions obtained from the results of interview trials and questionnaires. Keywords: Brand Campaign, Brand Awareness, Promotional Media, Environmentally Friendly, Handmade Soap